Does HIV/AIDS matter for economic growth in sub-Saharan Africa? - Anthony Mveyange; Christian Skovsgaard; Tine Lesner (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Estimating the impact of HIV/AIDS epidemic on economic growth is challenging because of endogeneity concerns. In this paper, we use novel data on male circumcision and distance from the first HIV outbreak as instrumental variables for the HIV/AIDS epidemic in 241 regions across 25 countries in sub-Saharan Africa during 2003-12. Our main finding shows that the impact of HIV/AIDS epidemic on economic growth is negative but statistically insignificant. Further investigation on the main channels through which HIV/AIDS may affect economic growth - namely human capital, population growth, and productivity - finds no impacts of the HIV/AIDS epidemic on these channels.
Keywords: I130; O110; O55; 330; HIV/AIDS; economic growth; endogeneity; sub-Saharan Africa